Analisis Laporan Laba Rugi PT Ramayana Lestari Sentosa Tbk Periode 2018-2022 - Lella Anita (CiDEA Journal, 2023)
The purpose of this study research is to determine the financial position of the retail company, namely PT Ramayana Lestari Sentosa Tbk in the last few years. The company's profit and loss report can be reviewed in the financial report to determine the company's financial condition. Each company has its own financial reports which aim to provide very useful information for both external and internal parties. Financial reports must be prepared in a structured and systematic manner. These reports are prepared as a form of management accountability to parties affected by the company's performance over a certain period of time. The Profit and Loss Report is a more comprehensive and detailed explanation of the company's financial results and costs over a certain period of time. This report is very useful for the business world, with one of its main objectives being to help the business world in making decisions regarding future actions.